Regulation of glucose utilization in adipose cells and muscle after long-term experimental hyperinsulinemia in rats. - L J Wardzala; M Hirshman; E Pofcher; E D Horton; P M Mead; S W Cushman; E S Horton (The Journal of Clinical Investigation, 1985)
The effects of chronic insulin administration on the metabolism of isolated adipose cells and muscle were studied. Adipose cells from 2 and 6 wk insulin-treated and control rats, fed either chow or chow plus sucrose, were prepared, and insulin binding, 3-O-methylglucose transport, glucose metabolism, and lipolysis were measured at various insulin concentrations. After 2 wk of treatment, adipose cell size and basal glucose transport and metabolism were unaltered, but insulin-stimulated transport and glucose metabolism were increased two- to threefold when cells were incubated in either 0.1 mM glucose (transport rate limiting) or 10 mM glucose (maximum glucose metabolism). Insulin binding was increased by 30%, but no shift in the insulin dose-response curve for transport or metabolism occurred. After 6 wk of treatment, the effects of hyperinsulinemia on insulin binding and glucose metabolism persisted and were superimposed on the changes in cell function that occurred with increasing cell size in aging rats. Hyperinsulinemia for 2 or 6 wk did not alter basal or epinephrine-stimulated lipolysis in adipose cells or the antilipolytic effect of insulin. In incubated soleus muscle strips, insulin-stimulated glucose metabolism was significantly increased after 2 wk of hyperinsulinemia, but these increases were not observed after 6 wk of treatment. We conclude that 2 wk of continuous hyperinsulinemia results in increased insulin-stimulated glucose metabolism in both adipose cells and soleus muscle. Despite increased insulin binding to adipose cells, no changes in insulin sensitivity were observed in adipose cells or muscle. In adipose cells, the increased glucose utilization resulted from both increased transport (2 wk only) and intracellular glucose metabolism (2 and 6 wk). In muscle, after 2 wk of treatment, both glycogen synthesis and total glucose metabolism were increased. These effects of hyperinsulinemia were lost in muscle after 6 wk of treatment, when compared with sucrose-supplemented controls.